1993
DOI: 10.1007/bf01352207
|View full text |Cite
|
Sign up to set email alerts
|

The influence of base metal grain size on isothermal solidification during transient liquid-phase brazing of nickel

Abstract: The influence of base metal grain size on isothermal solidification during transient liquid-phase brazing with Ni-11 wt% P filler metal has been investigated. Single-crystal, coarse-grained and fine-grained nickel base metal were brazed at 1150 ~ for various holding times. The eutectic width decreased linearly with the square-root of the brazing time in single-crystal, coarse-grained and fine-grained nickel base metals. The completion time for isothermal solidification decreased in the order single-crystal, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…The activation energy value found when bonding CMSX-2 base metal would be determined by the diffusion of boron into the solid substrates. In contrast, it is known that grain boundary regions influence the rate of isothermal solidification and that finer grain sizes promote the increased solute diffusion into the base metal [13]. It follows that the difference in activation energies between the single crystal and the polycrystal superalloys base metal can be readily explained by the fact that grain boundary regions can act as high diffusivity paths and these do not exist in single crystal material.…”
Section: Isothermal Solidification Processmentioning
confidence: 68%
“…The activation energy value found when bonding CMSX-2 base metal would be determined by the diffusion of boron into the solid substrates. In contrast, it is known that grain boundary regions influence the rate of isothermal solidification and that finer grain sizes promote the increased solute diffusion into the base metal [13]. It follows that the difference in activation energies between the single crystal and the polycrystal superalloys base metal can be readily explained by the fact that grain boundary regions can act as high diffusivity paths and these do not exist in single crystal material.…”
Section: Isothermal Solidification Processmentioning
confidence: 68%
“…The physical description of TLP bonding as a diffusioncontrolled phase change is well-established [4][5][6][7][11][12][13][14][15][16][17][18][19] and simulations made on this basis have been found to agree reasonably well with experimental observations [12,13]. Although the mathematical models used previously differ slightly from each other, there is general agreement on the nature of the underlying physical phenomena.…”
Section: Governing Equations and Boundary Conditionsmentioning
confidence: 89%
“…While some concerns have been expressed [5,12,[17][18][19] as to whether the interface remains planar during solidification if the parent material is polycrystalline, the process is usually modelled as illustrated schematically in Fig. 1.…”
Section: Governing Equations and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] The isothermal solidification time is reduced significantly with fine-grained base metal; the difference in isothermal solidification rates between coarsegrained and single-crystal base metal is negligible. [10,37,38] The increase in interface kinetics with finer grain size has been attributed to enhanced grain boundary diffusion and grain boundary grooving, although support for this theory by numerical modeling has only been qualitative to date. On the other hand, for coarse-grained substrates bonded at higher temperatures and longer isothermal hold times, it has been shown that the effect of grain boundaries on solid/ liquid interface motion is much less significant and can be considered with an effective diffusivity if required.…”
Section: Effect Of Grain Boundariesmentioning
confidence: 99%